2011
DOI: 10.1177/0269216311416696
|View full text |Cite
|
Sign up to set email alerts
|

Junior doctors’ learning and development in foundation year 1 posts in palliative medicine

Abstract: F1 posts in palliative medicine in the UK have positive influences on perceived generic skills development and practice. These findings might encourage the development of more rotations incorporating palliative medicine in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Furthermore, the methodologies employed and the points of assessment have limited the acknowledgment of the complexity of the experiences, particularly in the transition to junior doctors. 16 Our study provides a qualitative perspective to explore how junior doctors retrospectively view the benefits of undergraduate palliative care attachments. The attachments are clinical electives of three or four weeks, where medical students participate as if they were junior medical officers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the methodologies employed and the points of assessment have limited the acknowledgment of the complexity of the experiences, particularly in the transition to junior doctors. 16 Our study provides a qualitative perspective to explore how junior doctors retrospectively view the benefits of undergraduate palliative care attachments. The attachments are clinical electives of three or four weeks, where medical students participate as if they were junior medical officers.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,8 As other studies in similar settings have found, participants valued experiential, informal learning opportunities, particularly when interacting with patients and other staff. 9,10,16,17 Here, this experiential learning was achieved with suitable support from staff, but in other studies learning on the job has been described by junior doctors as being through making mistakes and being 'thrown in at the deep end'. 5,10 F1s placed emphasis on the role of senior doctors in informal learning.…”
Section: Discussionmentioning
confidence: 99%
“…Although already extant, this finding underlines the important educative role senior doctors have in supporting and teaching newly qualified doctors. 10,14,17 Some of the most valued learning opportunities were patient-related, for example, when given responsibility to do challenging tasks such as clerking new patients. Other research has also identified the importance of patient (or client)-centred tasks, being given responsibility and completing challenging tasks when learning in a workplace.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations